Determine the Potential Epitope Based Peptide Vaccine Against Novel SARS-CoV-2 Targeting Structural Proteins Using Immunoinformatics Approaches - Waqas, Muhammad; Haider, Ali; Sufyan, Muhammad; Siraj, Sami; Sehgal, Sheikh Arslan (Frontiers in Molecular Biosciences, 2020)
Abstract Coronaviruses (CoVs) are enveloped positive strand RNA viruses which have club-like spikes at the surface having a unique replication process and a large RNA genome (~25kb). Coronaviruses are known as one of major pathogenic viruses causing a variety of diseases in birds and mammals including humans (lethal respiratory dysfunctions). Nowadays, a new strain of coronaviruses is identified named as SARS -CoV-19, multiple cases of SARS-CoV-2 attacks are being diagnosed all over the World especially in China (Wuhan). SARS-CoV-2 showed high death rate exponentially, however, not even a single effective cure is being introduced yet against SARS-CoV-2. In current study, immunoinformatics approaches were employed to predict the antigenic epitopes against SARS-CoV-2 for the development of coronavirus peptide vaccine. Cytotoxic T-lymphocyte and B-cell epitopes were predicted for SARS-CoV-2 coronavirus structural proteins (Spikes, Membrane, Envelope and Nucleocapsid). The docking complexes of top 10 epitopes having antigenic sites were analyzed led by binding affinity and binding interactional analyses of top ranked predicted peptides with MHC-I HLA molecule. The predicted peptides may have potential to be used as peptide vaccine against the SARS-CoV-2.